Self-fashioning en Hispanoamérica en la época colonial (siglo XVII) - Böttcher, Nicolaus (Historamericana, 2021)
Based on autobiographical texts, the study draws a picture of colonial society in Hispanic America in the 17th century. The actors themselves have their say. At the same time, these texts serve to characterize the various population groups of post-Conquista colonial society.